PKM PEMBEKALAN MEMASUKI DUNIA KERJA ATAU KULIAH - Nur Elfi Husda (Jurnal Pengabdian Barelang, 2019)
Besides being able to work directly, vocational school graduates (SMK) can also continue to higher levels of education is universities, but choosing majors in higher education certainly adjusts to the interests and abilities of students. The problem that often occurs is the lack of students' knowledge about future plans so that many SMK graduates are actually unemployed, this is due to a lack of knowledge about preparing to enter the workforce and if they want to a student of univerities a lack of information about the majors to take and how to choose a good and right universities. To deal with these problems need to be given guidance to students about preparing to enter the world of work or college. The service method that is carried out is discourse method with two meetings and four different speakers. The first meeting was about how to get job information, how to make a cover letter, interview techniques and job interviews and how to choose the right major in universities. The second meeting with material about financial reporting using MYOB. From the distributed questionnaire the results show that students are satisfied with the lesson given and hope to become a regular agenda at school before students finish their education.